2015
DOI: 10.6001/biologija.v61i3-4.3206
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of Manilkara zapota (L.) fruits against Ehrlich ascites carcinoma in mice

Abstract: As a part of searching for potential anticancer agents from natural sources, this investigation was carried out to evaluate the antitumor effect of ethyl acetate extract of Manilkara zapota (L.) fruits (EEFM) against Ehrlich acsites carcinoma (EAC) in Swiss albino mice. The antitumour activity of EEFM has been evaluated against Ehrlich ascites carcinoma (EAC) at the doses of 50 and 100 mg/kg body weight. Treatment with EEFM (at 100 mg/kg body) showed a significant increase in the survival time and decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…The cytotoxic effect was further tested in HT-29 cells, which indicated that the aqueous leaf extract triggered morphological changes in cancer cells, induced apoptosis, promoted caspase-3 and caspase-8 activities, decreased MDA levels, elevated catalase levels, and upregulated mRNA levels. Khalek et al ( 67 ), tested the cytotoxicity of an ethyl acetate fruit extract in Ehrlich ascites carcinoma (EAC) cells where doses of 50 mg/kg and 100 mg/kg were administered. Results showed an increase in life span was found to be 41 and 67.7% and a cell growth inhibition of 47.5 and 65.7%, respectively.…”
Section: Mechanisms For Biological Activity and Medicinal Applicationsmentioning
confidence: 99%
“…The cytotoxic effect was further tested in HT-29 cells, which indicated that the aqueous leaf extract triggered morphological changes in cancer cells, induced apoptosis, promoted caspase-3 and caspase-8 activities, decreased MDA levels, elevated catalase levels, and upregulated mRNA levels. Khalek et al ( 67 ), tested the cytotoxicity of an ethyl acetate fruit extract in Ehrlich ascites carcinoma (EAC) cells where doses of 50 mg/kg and 100 mg/kg were administered. Results showed an increase in life span was found to be 41 and 67.7% and a cell growth inhibition of 47.5 and 65.7%, respectively.…”
Section: Mechanisms For Biological Activity and Medicinal Applicationsmentioning
confidence: 99%
“…Estos usos están relacionados con el alto contenido de compuestos fenólicos tanto en la cáscara como en la pulpa del fruto [11]. Además, estudios in vitro revelan que los frutos poseen una importante actividad antioxidante [12], antimicrobiana [13], antiinflamatorio [14] y antitumoral [15].…”
Section: Introductionunclassified
“…5,6 In addition, plants contain various molecular bioactive compounds, and consequently plant kingdom is a probable foundation of antineoplastic and cytotoxic agents. 7,8…”
Section: Introductionmentioning
confidence: 99%